Pengaruh Penggunaan Zat Pengatur Tumbuh Ausin (IBA) Terhadap Pertumbuhan Stek Batang Cincau Hijau (Cyclea Barbata Miers.) - Nurhidayat, Alfin; Sofyan, Antar; Rizali, Akhmad (Agroekotek View, 2023)
This study aims to determine the effect of the use of growth regulators (IBA) on the growth of green grass jelly stem cutting. This research was carried out at Loktabat Utara RT.05 RW.02, Loktabat, Banjarbaru City. The study was conducted from march 2020 to may 2020. The method used in this study was a single factor randomized block design (RBD). The treatment factor used was the concentration of auxin IBA solution with the concentration of K0 = 0 ppm; A1 = 50 ppm; A2 = 100 ppm; A3 = 150 ppm; A4 = 200 ppm. Each treatment was repeated four times to obtain 20 experiment. The variables observed were shoot length, number of shoots,number of leaves and percentage of growth. The results showed that giving a little concentration did not have a significant effect on the observed variables.